Retourner à la terre en Sardaigne, crises et installations en agriculture - Paula Dolci; Coline Perrin (Tracés, 2017)
This article offers a typology of the back-to-the-land migrations today in Sardinia (Italy). It is based on the assumption that the crisis in the cities of Southern Europe has accelerated the process of upgrading rural areas and agricultural activity. Building on a qualitative investigation, mixing interviews and participant observation, the article distinguishes different trajectories of return to land that show how the crisis acts rather as a trigger, as a catalyst of vocations within diverse profiles of new farmers. Addressed on an individual scale, these back-to-the-land migrations show thus different relationships to land and urbanity.